E-Planner Scheduling System (EPSS): Jotting Down and Managing Schedule Online - Akmal Rosli, Muhammad Danial; Saad, Sharhida Zawani (Multidisciplinary Applied Research and Innovation, 2023)
With the rapid growth of technology nowadays, the usage of papers and manual ways to write on organizers, planners or diaries gradually become obsolete, although not in a complete manner. People are much attached to devices such as smartphones, PCs or tablets to do various tasks such as writing notes and planning schedules and activities. These devices provide more convenience and the benefit of mobile features, easy to carry anywhere and anytime. The objectives of this work are to identify requirements, develop the E-Panner Scheduling System (EPSS) and evaluate the usability of the system. The EPSS can benefit students in planning any meeting schedules, academic programs or marking the dates for important events such as exams, quizzes, crucial assessments, academic calendars or even semester breaks. The methodology used is the Rapid Application Development (RAD) model, due to the flexibility of the method that allows amendments or modifications easily from time to time. Also, the cycle time of the project could be reduced through the usage of reusable existing components. To evaluate the project’s usability, a field study was conducted and the results based on the evaluation proved that the EPSS is convenient to be used. The study contributes toward a comprehension of the requirements of the system and the user interface of a Web-based system to handle and manage crucial tasks and activities more efficiently in supporting today’s active and demanding lifestyles. It can be a reference model for similar Web applications or enhance the capabilities in organizing and managing routines, schedules and events better.